Compounded and raw rubbers for bitumen modification - Nagurskyy, Andriy; Grynyshyn, Oleg; Khlibyshyn, Yuriy; Antoshkiv, Dmytro (Видавництво Львівської політехніки, 2017)
The analysis of petroleum bitumen characteristics used in road building is presented. The inflence of crumb rubber derived from waste tires on the bitumen properties has been investigated. The modification residual bitumen polymer latexes Butonal NS 198 and Butonal NS 104 and the analysis of modified bitumen. Using the above-mentioned products it is possible to omprove bitumen properties
Keywords: bitumen; rubber-bitumen blinder rubber crumb; bitumen modification; swelling